2021
DOI: 10.1021/acsami.1c06029
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Investigation of a Slight Overcharge on Degradation and Thermal Runaway Behavior of Lithium-Ion Batteries

Abstract: Overcharge is a hazardous abuse condition that has dominant influences on cell performance and safety. This work, for the first time, comprehensively investigates the impact of different overcharge degrees on degradation and thermal runaway behavior of lithium-ion batteries. The results indicate that single overcharge has little influence on cell capacity, while it severely degrades thermal stability. Degradation mechanisms are investigated by utilizing the incremental capacity–differential voltage and relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…In this work, four peaks of IC curve appear. Generally, the loss of lithium inventory (LLI) will cause the area of peak ① to decrease, while the loss of active material (LAM) will decrease the areas of other peaks. , Besides, conductivity loss (CL) will cause the IC curve to shift to a lower voltage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, four peaks of IC curve appear. Generally, the loss of lithium inventory (LLI) will cause the area of peak ① to decrease, while the loss of active material (LAM) will decrease the areas of other peaks. , Besides, conductivity loss (CL) will cause the IC curve to shift to a lower voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Phase transition, transition-metal dissolution and electrode oxidation for the cathode, 28,29 and lithium plating for the anode will happen during the overcharge process, 30 which seriously deteriorates the thermal stability of the lithium-ion battery. 23 From the above analysis, it can be concluded that electrical abuse has a severe impact on the life and safety of lithium-ion batteries. Previous research mainly focused on the impact caused by overcharge or over-discharge, respectively, and did not compare the effects of overcharge and over-discharge on lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations